Determination of accurate electron chiral asymmetries in fenchone and camphor in the VUV range: sensitivity to isomerism and enantiomeric purity - Nahon, Laurent; Nag, Lipsa; Garcia, Gustavo A.; Myrgorodska, Iuliia; Meirerhenrich, Uwe; Beaulieu, Samuel; Wanie, Vincent; Blanchet, Valerie; Geneaux, Romain; Powis, Ivan (Royal Society of Chemistry, 2016)
Photoelectron circular dichroism (PECD) manifests itself as an intense forward/backward asymmetry in the angular distribution of photoelectrons produced from randomly-oriented enantiomers by photoionization with circularly-polarized light (CPL). As a sensitive probe of both photoionization dynamics and of the chiral molecular potential, PECD attracts much interest especially with the recent performance of related experiments with visible and VUV laser sources. Here we report, by use of quasi-perfect CPL VUV synchrotron radiation and using a double imaging photoelectron/photoion coincidence (i2PEPICO) spectrometer, new and very accurate values of the corresponding asymmetries on showcase chiral isomers: camphor and fenchone. These data have additionally been normalized to the absolute enantiopurity of the sample as measured by a chromatographic technique. They can therefore be used as benchmarking data for new PECD experiments, as well as for theoretical models. In particular we found, especially for the outermost orbital of both molecules, a good agreement with CMS-X PECD modeling over the whole VUV range. We also report a spectacular sensitivity of PECD to isomerism for slow electrons, showing large and opposite asymmetries when comparing R-camphor to R-fenchone (respectively -10% and +16 % around 10 eV). In the course of this study, we could also assess the analytical potential of PECD. Indeed, the accuracy of the data we provide are such that limited departure from perfect enantiopurity in the sample we purchased could be detected and estimated in excellent agreement with the analysis performed in parallel via a chromatographic technique, establishing a new standard of accuracy, in the ±1 % range, for enantiomeric excess measurement via PECD. The i2PEPICO technique allows correlating PECD measurements to specific parent ion masses, which would allow its application to analysis of complex mixtures.